Islamic ecoteology and the spirit of fastabiqul khairat: A reconstruction of the theology of goodness in the era of ecological crisis and digital public space - Yudaningsih, Yudaningsih; Solihin, Muhtar; Munir , Munir (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the relationship between Islamic theology and the global ecological crisis through the perspective of Islamic ecotheology. The main focus is to explore the principles of monotheism, khalifah, and amanah as the basis for the formation of Islamic ecological ethics relevant to the development of sustainable civilization in the modern era. This study employs a qualitative approach, utilising library research methods. Data were obtained from primary and secondary literature related to Islamic theology, environmental ethics, and ecological spirituality. The analysis was conducted descriptively and reflectively, using an interpretative model to examine ecotheological values within the context of the global environmental crisis. This study found that Islamic ecotheological values have the potential to build a theology of a good paradigm that integrates faith, knowledge, and ecological action. The principle of Fastabiqul Khairat (competing in goodness) can serve as a theological basis for encouraging environmental action and interfaith digital da'wah as a form of spiritual responsibility towards the earth. The results of this study can be applied in various fields, including Islamic education, environmental ethics, social theology, and digital communication studies. These findings are also relevant to the development of public policy, socio-religious movements, and ecology-based da'wah strategies that strengthen spiritual awareness and environmental sustainability. This research presents a reconstruction of the theology of goodness, drawing on Islamic ecotheology and its integration with digital culture. This approach expands the role of Islamic theology from the normative realm to collaborative ecological praxis, making a new contribution to the development of environmental theology discourse in the global era.